Integrated nutrient management for improving crop yields, soil properties, and reducing greenhouse gas emissions - Paramesh, Venkatesh; Mohan Kumar, R.; Rajanna, G. A.; Gowda, Sathish; Nath, Arun Jyoti; Madival, Yamanura; Jinger, Dinesh; Bhat, Shripad; Toraskar, Sulekha (Frontiers in Sustainable Food Systems, 2023)
Recently, most agrarian countries have witnessed either declining or stagnant crop yields. The lack of soil organic matter (SOM) due to the poor physical, chemical, and biological properties of the soil leads to an overall decline in the productivity of farmlands. Therefore, the adoption of integrated nutrient management (INM) practices is vital to revive sustainable soil health without compromising yield potential. INM is a modified nutrient management technique with multifarious benefits, wherein a combination of all possible sources of plant nutrients is used in a crop nutrition package. Several studies conducted in various parts of the world have demonstrated the benefits of INM in terms of steep gain in soil health and crop yields and at the same time, reducing greenhouse gas emissions and other related problems. The INM practice in the cropped fields showed a 1355 % reduction in methane over conventional nutrient management. The increase in crop yields due to the adoption of INM over conventional nutrient management was as high as 1.3 to 66.5 % across the major cropping systems. Owing to the integration of organic manure and residue retention in INM, there is a possibility of significant improvement in soil aggregates and microbiota. Furthermore, most studies conducted to determine the impact of INM on soil health indicated a significant increase in overall soil health, with lower bulk density, higher porosity, and water-holding capacity. Overall, practicing INM would enhance soil health and crop productivity, in addition to decreasing environmental pollution, greenhouse gas emissions, and production costs.